Communication networks do not predict success in attempts at peer production. Issue 3 (16th March 2023) - Foote, Jeremy; Shaw, Aaron; Hill, Benjamin Mako
Abstract: Although peer production has created valuable information goods like Wikipedia, the GNU/Linux operating system, and Reddit, the majority of attempts at peer production achieve very little. In work groups and teams, coordination and social integration—manifested via dense, integrative communication networks—predict success. We hypothesize that the conditions in which new peer production communities operate make communication problems common and make coordination and integration more difficult, and that variation in the structure of project communication networks will predict project success. In this article, we measure communication networks for 999 early-stage peer production wikis. We assess whether communities displaying network markers of coordination and social integration are more productive and long-lasting. Contrary to our expectations, we find a very weak relationship between communication structure and collaborative performance. We propose that technology may serve as a partial substitute for communication in coordinating work and integrating newcomers in peer production. Lay Summary: Most attempts at online collaborative production start small and never gain more than a few contributors. One possible explanation is that new communities struggle to coordinate their work and integrate their members. When coordination and social integration are working well in offline groups, a group's communication networks are inclusive and dense. We look for evidence of the importance of coordination and integration processes by testing whether communication network structures in 999 early-stage wikis help to predict whether the wiki is productive and how long it stays active. We find little relationship between network structures and performance, and we discuss how technology may partially substitute for communication in coordinating and integrating members.